2008
DOI: 10.1021/jp8024717
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Electron Transfer Kinetics at the Ionic Liquid/Metal Interface Studied Using Cyclic Voltammetry and Scanning Electrochemical Microscopy

Abstract: The electrochemical behavior of a redox-active, ferrocene-modified ionic liquid (1-ferrocenylmethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide) in acetonitrile and in an ionic liquid electrolyte (1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide) is reported. Reversible electrochemical behavior was observed in each electrolyte with responses typical of those for unmodified ferrocene observed in each medium. In the ionic liquid electrolyte, the diffusion coefficient of the redox-active io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 53 publications
5
48
1
Order By: Relevance
“…Also, these results are in the same order of magnitude with those reported in literature [46]. One of the great advantages of EIS is that an independent check of the validity of impedance data is possible through the use of the Kramers-Kronig transforms [44].…”
Section: Half-wave Potentials and Heterogeneous Electron Transfer Kinsupporting
confidence: 80%
See 1 more Smart Citation
“…Also, these results are in the same order of magnitude with those reported in literature [46]. One of the great advantages of EIS is that an independent check of the validity of impedance data is possible through the use of the Kramers-Kronig transforms [44].…”
Section: Half-wave Potentials and Heterogeneous Electron Transfer Kinsupporting
confidence: 80%
“…Accordingly, care must be taken during the analysis of approach curves for a viscous medium such as an RTIL. Recently, it has been reported that SECM allows a better determination of the kinetic parameters in RTILs [46]. However, better control of the hydrodynamic regime is necessary in order to obtain stationary SECM approach curves.…”
Section: Electrochemical and Secm Responses Of Neat Fcemitfsi At 50°cmentioning
confidence: 99%
“…For a simple quasi-reversible redox reaction at a disc-shaped SECM tip, coupled with the diffusion-controlled regeneration of the mediator at the substrate, the normalised tip current at potential E is given by [22]: [44]. In this case, the k 0 value obtained from fitting the experimental data to Eq.…”
Section: Studying Electron Transfer In Rtils Using Secmmentioning
confidence: 99%
“…Our studies and others have shown that the capacitance of IL/electrode interface is potential dependent, and the adsorption of gas on the IL/electrode interface will decrease the double-layer capacitance under a specific DC bias potential [80]. In contrast to the EDL typically observed in dilute aqueous or nonaqueous electrolytes, the ions of ILs are strongly oriented near the electrode into an ordered layer structure with local ion density at maximum possible value [81,82]. Multiple ion pair layers form at the interface of IL and metal electrode.…”
Section: Charging Current In CVmentioning
confidence: 63%